Notice of Availability: Notice of Funding Availability (NOFA) for HUD's Fiscal Year (FY) 2011 Lead-Based Paint Hazard Control Grant Program and Lead Hazard Reduction Demonstration Grant Program and Amendment and Technical Corrections (The Federal Register / FIND, 2011)
Notice of Availability and Technical Amendment and Technical Corrections to the Notice of Funding Availability (NOFA) for HUD's Fiscal Year (FY) 2011 Lead-Based Paint Hazard Control Grant Program and Lead Hazard Reduction Demonstration Grant Program, FR-5500-N-02. Citation: "76 FR 28803" Document Number: "Docket No. FR-5500-N-02" Page Number: "28803" "Notices" SUMMARY: On April 8, 2011, HUD posted the Notice of Funding Availability (NOFA) for the Fiscal Year (FY) 2011 Lead-Based Paint Hazard Control Grant Program and Lead Hazard Reduction Demonstration Grant Program to Grants.gov (FR-5500-N-02). The NOFA announced the availability of information on applicant eligibility, submission deadlines, funding criteria, and other requirements for HUD's FY2011 Lead-Based Paint Hazard Control Grant Program and Lead Hazard Reduction Demonstration Grant Program. The posted NOFA indicated that the total amount of funding available was subject to enactment of HUD appropriations. On May 10, 2011, HUD posted an amendment to the NOFA which provided the funding available as a result of enactment of the HUD appropriations Act, the Department of Defense and Full-Year Continuing Appropriations Act, 2011, Public Law 112-10, approved April 15, 2011, and other technical Corrections. Based on the enactment of the FY2011 HUD appropriations, approximately $95.5 million is available for the programs in this NOFA. Of this amount, approximately $47.5 million is available for the Lead-Based Paint Hazard Control Program and $48 million for the Lead Hazard Reduction Demonstration Grant Program. The notice also amended the deadline date for applications and made other technical corrections to the NOFA. As a result of these technical corrections, the new deadline date for this NOFA is 11:59:59 p.m. June 10, 2011. The purpose of the Lead-Based Paint Hazard Control Grant Program and the Lead Hazard Reduction Demonstration Grant Program is to assist states, Native American Tribes, cities, counties/parishes, or other units of local government in undertaking comprehensive programs to identify and control lead-based paint hazards in eligible privately owned rental or owner-occupied housing with the exception that the Lead Hazard Reduction Demonstration Grant Program is targeted to urban jurisdictions with the greatest lead-based paint hazard control needs. The notice providing information regarding the application process, funding criteria and eligibility requirements, application and instructions, and amendment and technical corrections can be found using the Department of Housing and Urban Development agency link on the Grants.gov/Find Web site at http://www.grants.gov/search/agency.do. A link to the funding opportunity is also available on the HUD Web site at http://portal.hud.gov/hudportal/HUD?src=/program_offices/administration/grants/fundsavail. The link from the funds available page will take you to the agency link on Grants.gov. The Catalogue of Federal Domestic Assistance (CFDA) number for the Lead Hazard Reduction Demonstration program is 14.900. The Catalogue of Federal Domestic Assistance (CFDA) number for the Lead Hazard Reduction Demonstration program is 14.905. Applications must be submitted electronically through Grants.gov.